Rapid progression of carcinoma en cuirasse breast dermal metastases on 18F-fludeoxyglucose positron emission tomography–computed tomography - Young, Colin Raymond; Harigopal, Mallini; Pucar, Darko (World Journal of Nuclear Medicine, 2020)
Cancer in the dermis of the breast has a poor prognosis. The breast dermis can become malignantly involved primarily in inflammatory breast cancer, through the direct extension of locally advanced breast cancer, or metastatically from an underlying breast mass or a distant primary malignancy (e.g., gastric adenocarcinoma). Breast dermal metastases have the shortest median survival among them. Breast dermal metastases are classified into eight clinicohistopathologic groups, one of which is carcinoma en cuirasse. We present a case of a 52-year-old female with a history of invasive ductal carcinoma, Stage IIIC (pT2N3a), treated with lumpectomy, axillary node dissection, and chemoradiation therapy that recurred as carcinoma en cuirasse breast dermal metastases. Through 18F-fludeoxyglucose positron emission tomography–computed tomography (18F-FDG PET-CT) and clinical images, the case illustrates the rapid progression and devastating consequences of carcinoma en cuirasse breast dermal metastases over a 4-month period despite optimal therapy. Furthermore, the case emphasizes the sensitivity of 18F-FDG PET-CT to detect pathology in the breast dermis. Finally, the case highlights the crucial role that nuclear medicine physicians play in helping clinical colleagues differentiate between the various breast dermal malignant manifestations and benign mastitis, a common confounder in postradiation patients.
Keywords: 18F-fludeoxyglucose positron emission tomography–computed tomography; breast dermal metastases; carcinoma en cuirasse; inflammatory breast cancer; locally advanced breast cancer